Assessing surface water quality in Fayoum, Egypt using an integrated WQI-GIS approach for multi-purpose reuse - Refaai, Mostafa Gaber; El-Sherbeeny, Ahmed M.; Alqhtani, Haifa A.; Allam, Ahmed A.; Abukhadra, Mostafa R.; Al Zoubi, Wail; Wahed, Mahmoud S. M. Abdel (Frontiers in Environmental Science, 2025)
Water quality management remains a critical challenge in arid and semi-arid regions, where limited freshwater resources are increasingly stressed by anthropogenic activities and natural constraints. This study provides a summer 2024 assessment of surface water quality in Egypt’s Fayoum Governorate, emphasizing spatial variability, dominant pollution drivers, and sectoral suitability. Ten sites across agricultural drains and wastewater discharge points were analyzed for 17 physicochemical parameters. The Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI) was applied to evaluate drinking, irrigation, industrial, and ecological uses, while spatial patterns were mapped using Inverse Distance Weighting (IDW) in a Geographic Information System. The results reveal critical exceedances in salinity (TDS up to 3,420 mg/L; EC up to 6,840 μS/cm), nutrient enrichment (PO43− up to 10.85 mg/L; NH3–N up to 10.78 mg/L), and turbidity (105 nephelometric turbidity units), mainly from untreated sewage, agricultural return flows, and limited dilution. WQI classification for drinking water showed 30% good, 50% fair, and 20% poor (<45), with S9 and S10 posing high health risks due to cumulative sewage, industrial discharges, and intensive farming runoff. For irrigation, 60% of sites were rated good, though elevated sodium, magnesium hazard, and potential salinity indicate risks of soil degradation. Industrial assessments revealed scaling (LI >0) and corrosion (RSI >8.5) in more than half the samples. Ecologically, 50% of sites recorded poor WQI (<45), reflecting eutrophication, organic load, and elevated temperatures. CCME-WQI/GIS mapping identified S9 and S10 as hotspots, concentrated near Lake Qarun where pollutant accumulation is intensified by weak hydrological flushing. The contrasting signatures of nutrient-enriched agricultural drains and salinity-dominated industrial reaches underscore the need for targeted interventions. Strengthening wastewater treatment, optimizing fertilizer use, enforcing standards, and enhancing public awareness are recommended. The integrated CCME-WQI/GIS framework offers a replicable tool for sustainable water management in arid, agriculture-dependent regions and supports progress toward Sustainable Development Goal 6.